2022
DOI: 10.17358/jabm.8.3.758
|View full text |Cite
|
Sign up to set email alerts
|

Choosing Herbal Toothpaste: Study on Consumer Behavior and Preferences in The Greater Jakarta Area

Abstract: The research aims are investigating consumers' psychology and behavioral characteristics and investigating the consumer's characteristics that affects experienced preferences in the Greater Jakarta Area. Consumer profile and consumer behavior were carried out using descriptive statistics analysis and cross tabulation analysis. Meanwhile, to measure consumer preferences for herbal toothpastes, logistic regression analysis (logit) was used. This survey was conducted on 459 respondents in the Greater Jakarta area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In contrast, earlier studies in the Kurdistan Region, Iraq, and Indonesia revealed a female predominance in the herbal industry. These ndings may have been in uenced by the cultural contexts of the two studies as well as the nature of the diseases being studied; for instance, their study concentrated on toothpaste herbs, which are more popular among women [33,34]. According to [34] ndings in the Kampala district, the majority of participants elderly( 51 to 55), which is older than the ideal and admirable range of 31 to 45 for the continuation, expansion, and sustainability of the herbal business and endangers its existence [35].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, earlier studies in the Kurdistan Region, Iraq, and Indonesia revealed a female predominance in the herbal industry. These ndings may have been in uenced by the cultural contexts of the two studies as well as the nature of the diseases being studied; for instance, their study concentrated on toothpaste herbs, which are more popular among women [33,34]. According to [34] ndings in the Kampala district, the majority of participants elderly( 51 to 55), which is older than the ideal and admirable range of 31 to 45 for the continuation, expansion, and sustainability of the herbal business and endangers its existence [35].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the education of people regarding the importance of oral hygiene maintenance, proper selection of oral hygiene products is essential (Logaranjani et al 2015). In present study, customer expectations, usage, attitude and brand comparison were studied for the toothpaste category, wherein the primary benefits that the consumer seeks while using a particular brand was analyzed with its purchasing pattern and behavior, and the core triggers to purchase their favorite brand (Dani, 2013, Vaikunthavasan 2014, Septiani, et al 2022. The effect of demographic factors like age, gender, occupation, income level was observed with respect to the purchase of toothpaste.…”
Section: Introductionmentioning
confidence: 99%